Information literacy meets “Research 2.0”: exploring developments in Croatian academic libraries - Špiranec, Sonja (Array, 2012)
Information literacy training for researchers should be determined by information needs of scholars and by reconfiguration of information environments. New research environments, which are a result of technological innovations initiated by Web 2.0, have the potential to change the very principles of science and research. In the paper the authors analyze the main features of research practices that rely on Web 2.0 tools and comment on re-conceptualizations of IL training for researchers that are a consequence of such “Research 2.0” transitions. The main idea behind IL re-conceptualizations is that libraries have to concentrate less on the traditional IL paradigm which focused heavily on resource discovery and especially on traditional library tools, while dealing more with evaluation, information management, authority issues and a range of new concerns brought about by Web 2.0. The paper presents a survey of the deployment of conceptual adaptations in IL in the context of Croatian academic libraries. The study showed that libraries concentrate on a relatively narrow subset of IL in the form of traditional library topics such as searching and finding sources in libraries and academic databases. The authors suggest that new approaches are needed to make IL sessions for researchers more relevant and truly meaningful.